Cementum status in natural teeth opposing implant-borne bridgework in Macaca fascicularis - Siar, C.H.; Pua, C.K.; Toh, C.G.; Romanos, G.; Ng, K.H. (2012)
Objective. The objective of this study was to investigate the cementum status in natural teeth opposing implant-supported bridgework. Methods. Maxillary premolars and molars opposing immediate-loading (IL) and delayed-loading (DL) mandibular implant-supported bridgework in 4 Macaca fascicularis were harvested after 3 months of functional loading. Another 2 monkeys without mandibular fixed prostheses served as control. The cervical (CCW) and apical cementum width (ACW), and resorption craters (RCs) were measured. Results. No significant differences were observed between test and control groups for mean CCW (control = 26.79 +/- 3.28, IL = 21.29 +/- 9.12, and DL = 20.32 +/- 5.65 mu m) and for ACW (control = 937.97 +/- 353.74, IL = 955.26 +/- 720.05, and DL = 750.56 +/- 517.26 mu m) (P > .05). In test and control monkeys, RCs were uncommon and showed no significant differences in width (control = 0.71 +/- 0.38, IL = 1.02 +/- 0.49, DL = 0.85 +/- 1.02 mm) and depth (control = 0.15 +/- 0.07, IL = 0.25 +/- 0.40, DL = 0.22 +/- 0.15 mm) (P > .05). Conclusions. Present findings suggest that implant-supported bridgework does not produce any adverse effects on the cementum of opposing natural teeth after 3 months of functional loading. (Oral Surg Oral Med Oral Pathol Oral Radiol 2012;114(suppl 5)(suppl 5):S46-S53)